Trust yourself and trust the students! Lessons learned from ditching straight lecturing and using arts-based strategies in the classroom - Sharon Martinelli; Michelle Camilleri (Science Talks)
In today's digital world, where information is literally out there at a click of a button, the approach to teaching and learning needs to change. Through our study unit on personal and professional growth and development, we transitioned from disruptors to innovators. We accomplished this by adopting a radically new approach to our teaching and learning processes using an arts-based lens so as to impact their growth and development as student nurses. Participation in the study was entirely voluntary. We designed a web-based survey of Likert scales and open-ended questions to explore students' perspectives on the approach to teaching and learning adopted. Data was also collected from students' reflective writing excerpts. Data from ourselves as educators was captured through ongoing conversations. Data was analysed using simple descriptive statistics for the quantitative data as well as thematic analysis for the text data. The findings show that the teaching and learning approach was well received as it was found to be situational, dynamic, engaging, active and above all relevant.Similarly, as educators we observed significant growth and development in our students throughout the study unit, which was captured through the changing nature of the discussions, the engagement in the activities as well as changes to the writing overtime. There are wide ranging implications of our findings. Educators need to make a shift from imparting knowledge to the co-creation and generation of new knowledge or new understandings. Students will engage if the learning is meaningful to them, and when this is done in a collaborative manner.